SINERGITAS KOMUNIKASI GURU PENGAJIAN DAN GURU RUPAKA DALAM MEMBANGUN KESIAPAN BELAJAR PADA ANAK USIA DINI DI KABUPATEN TULANG BAWANG LAMPUNG - Ni Nyoman Sudiani (JARITA : Journal of Children’s Education and Learning Research, 2026)
This research examines the synergy of communication between study teachers and rupaka teachers in building early childhood learning readiness in Tulang Bawang Lampung. There is a lack of learning readiness in early childhood at Badik Alam 2 Kindergarten and Hosana Kindergarten because there are children who are still dependent on their parents. Parents are told to wait in class so that children have very little independence and they don't interact with their peers. This study used descriptive qualitative method. The research wants to know the synergy of communication between study teachers and parents so that it can build learning readiness in early childhood, and to find out the implications of synergistic communication between recitation teachers and art teachers. Research results: 1) The importance of collaboration between teachers and parents in building learning readiness in early childhood, and Interpersonal communication to overcome factors that cause children not to be independent, such as meeting teachers with parents and training children to be independent by allowing them to wait outside the classroom; and 2) The impact of collaboration between the recitation teacher and the art teacher is that the child is independent, not fussy, the teacher can guide the child comfortably, the child wants to play with friends, and the parents are not worried.